Anesthetic Management of a Child with Severe Hydrocephalus, Predicted Difficult Airway, Obstructive Ileus, and Sepsis Undergoing Exploratory Laparotomy: A Case Report - Ardana Tri Artanto; Aura Ihsaniar; Joni Riana Mustaqim (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Severe hydrocephalus with macrocephaly creates a predicted difficult airway and raised intracranial pressure (ICP), a challenge magnified when it coexists with obstructive ileus and sepsis. The simultaneous demand to protect the brain, secure a distorted airway, prevent aspiration, and preserve perfusion in a septic, malnourished child makes anesthetic planning exceptionally complex. Case presentation: A 5-year-old boy with cerebral palsy and untreated severe communicating hydrocephalus (head circumference 81 cm) presented with vomiting, abdominal distension, and obstipation. He was septic, severely dehydrated, and marasmic, with imaging confirming severe hydrocephalus, agenesis of the corpus callosum, and low small-bowel obstruction. Exploratory laparotomy was prioritized over ventriculoperitoneal shunting. Anesthesia used a modified rapid sequence induction with a ketamine-based regimen and ramp positioning to align the head-body axis for intubation. Surgery lasted 2.5 hours with stable hemodynamics. The child was transferred intubated to the pediatric intensive care unit for controlled ventilation and neurological monitoring. Conclusion: Integrated, individualized planning allowed safe anesthesia in a child with colliding neurological, surgical, infectious, and nutritional emergencies. A ketamine-based modified rapid sequence induction with ramp positioning, neuroprotective maintenance, surgical sequencing, and planned postoperative ventilation balanced ICP control against septic hemodynamic stability.